D-Stability Analysis of Descriptor Systems and Application in Power Systems - Verdejo-Fredes, H; Acosta-Barbosa, K (IEEE Computer Society, 2015)
This paper focuses on D-stability analysis problem for descriptor systems in algebraic differential representation. Necessary and sufficient conditions are proposed in order to ensure that all system eigenvalues belongs to a given set in the complex plane. Note that, the location of the eigenvalues in the study of dynamic systems is an important aspect to be considered since it allows obtaining important information about the system s response. The proposed results are described as a set of LMIs and are applied to a single-machine infinite-bus power system. © 2015 IEEE.